2022
DOI: 10.1002/advs.202105368
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Defects and Microstructures in Ferroelectrics for Enhanced/Novel Properties: An Emerging Way to Cope with Energy Crisis and Environmental Pollution

Abstract: In the past century, ferroelectrics are well known in electroceramics and microelectronics for their unique ferroelectric, piezoelectric, pyroelectric, and photovoltaic effects. Nowadays, the advances in understanding and tuning of these properties have greatly promoted a broader application potential especially in energy and environmental fields, by harvesting solar, mechanical, and heat energies. For example, high piezoelectricity and high pyroelectricity can be designed by defect or microstructure engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 264 publications
(574 reference statements)
1
20
0
Order By: Relevance
“…Especially, in the current situation, when the COVID-19 epidemic is complicated, the logistics port ensures the distance between people, thereby minimizing the possibility of cross-infection in the community (Kosiek et al, 2021). As the Covid-19 pandemic subsides, the world is immersed in the price storm of the energy crisis due to the sharp increase in oil prices (Dong et al, 2022). The shipping industry is being strongly impacted by this energy crisis.…”
Section: Concept and Development History Of Smart Portmentioning
confidence: 99%
“…Especially, in the current situation, when the COVID-19 epidemic is complicated, the logistics port ensures the distance between people, thereby minimizing the possibility of cross-infection in the community (Kosiek et al, 2021). As the Covid-19 pandemic subsides, the world is immersed in the price storm of the energy crisis due to the sharp increase in oil prices (Dong et al, 2022). The shipping industry is being strongly impacted by this energy crisis.…”
Section: Concept and Development History Of Smart Portmentioning
confidence: 99%
“…Ferroelectrics with the intrinsic nature of spontaneous polarization are a class of intriguing piezoelectrics that exhibit larger piezoelectric coefficients and thus higher piezocatalytic activities . More importantly, when ferroelectrics are light-excited, spontaneous polarization-induced internal electric field (IEF) provides a driving force to separate photocreated electrons and holes toward opposite sides. As such, photoelectrons and holes accumulated at two opposite ends (one is positively charged and another one is negatively charged) enable the formation of spatially separated reduction and oxidation cocatalysts suitable for piezocatalysis and piezophotocatalysis via selective photoreduction and oxidation of metal salts on positive and negative domains, respectively. Inspired by this, in this work, we demonstrate the selective photodeposition of spatially separated redox cocatalysts on oppositely poled facets of ferroelectrics for significantly enhanced piezophotocatalytic activity in overall CO 2 reduction and H 2 O oxidation. With PbTiO 3 nanoplates, which can be excited under both stress and light, as a model ferroelectric, it is found that the synergistic interplay of the spatially separated AuCu reduction cocatalyst and the MnO x oxidation cocatalyst contributes to the highest charge separation efficiency and optimal surface reactivity, thus producing the most greatly enhanced piezocatalytic, photocatalytic, and piezophotocatalytic performance in CO and O 2 production as compared with sole AuCu, MnO x , and randomly deposited AuCu/MnO x cocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various approaches (doping, , defect engineering, , etc., for ceramic materials and ceramic filler inclusion, electrospinning, , etc., for polymer materials) have been utilized to amplify the output properties of PEH. On the other hand, for TEH, output power density, which is a measure of its superiority, mainly depends on the dielectric constant and surface charge density of the triboelectric layers .…”
Section: Introductionmentioning
confidence: 99%